2008
DOI: 10.1902/jop.2008.070566
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Submandibulectomy on Alveolar Bone Loss in Rats

Abstract: Sx has a deleterious effect on the periodontal tissues, particularly marginal alveolar bone, indicating the importance of the submandibular/sublingual glands in maintaining healthy periodontal conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 23 publications
1
32
0
3
Order By: Relevance
“…Reduced salivary secretion can increase the numbers of pathological bacteria, and induce oral diseases such as periodontitis [11,12]. In this regard, we have previously reported that submandibulectomy has a deleterious effect on the periodontal tissues, particularly marginal alveolar bone, indicating the importance of this gland in maintaining healthy periodontal conditions [53]. We demonstrated that histamine treatment augmented salivary secretion of SMG from rats with EP.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Reduced salivary secretion can increase the numbers of pathological bacteria, and induce oral diseases such as periodontitis [11,12]. In this regard, we have previously reported that submandibulectomy has a deleterious effect on the periodontal tissues, particularly marginal alveolar bone, indicating the importance of this gland in maintaining healthy periodontal conditions [53]. We demonstrated that histamine treatment augmented salivary secretion of SMG from rats with EP.…”
Section: Discussionmentioning
confidence: 59%
“…** P \ 0.01, *** P \ 0.001 vs. control. ## P \ 0.01, ### P \ 0.001 vs. experimental periodontitis data in which EP produced a two-fold increase in alveolar bone loss [15,53,55]. Interestingly, this detrimental effect was diminished by histamine treatment.…”
Section: Discussionmentioning
confidence: 97%
“…The submandibular gland (SMG) is one of the major salivary glands, together with the parotid and sublingual glands 13 . Under physiologic conditions, the protective potential is sufficiently maintained by salivary flow; however, this state seems to be disturbed in periodontitis, as reported by Amer et al 14 It was demonstrated that in rats subjected to ligature‐induced periodontitis, SMG salivary secretion diminishes and changes in composition, and the alteration of salivary flow and composition was shown to aggravate periodontitis 15 …”
mentioning
confidence: 97%
“…2013). Alveolar bone loss is a common consequence of periodontitis, an infectious disease characterized by inflammation of toothsupporting tissues and by periodontal pocket formation, which also results in loss of periodontal attachment tissue with evidence that indicates the role of SMG in the regulation of immune/inflammatory reactions (Vacas et al, 2008). Periodontal disease is associated with inflammatory markers in gingival .…”
Section: Discussionmentioning
confidence: 99%